2017
DOI: 10.2337/dc17-1042
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycan Profile and Kidney Disease in Type 1 Diabetes

Abstract: Higher HbA in type 1 diabetes is associated with changes in the serum N-glycome that have elsewhere been shown to regulate the epidermal growth factor receptor and transforming growth factor-β pathways that are implicated in DKD. Furthermore, N-glycans are associated with ACR and eGFR slope. These data suggest that the role of altered N-glycans in DKD warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 40 publications
4
74
0
Order By: Relevance
“…A majority of studies in this area focused on UDP-GlcNAc stimulation of O-glycosylation (O-glycosidic linkage between glycan and an amino acid containing a hydroxyl group [77]) when discussing the possible mechanism of diabetic complications as a consequence of increased flux through HBP [78,79]. In a recent study, we have demonstrated that serum N-glycan alterations are associated with diabetic kidney disease [40], which is further discussed below. Taken together, there is accumulating evidence for the role of HBP in both diabetes onset and diabetes complications.…”
Section: Hexosamine Biosynthesis Pathway and Its Role In Diabetes Thrmentioning
confidence: 99%
See 3 more Smart Citations
“…A majority of studies in this area focused on UDP-GlcNAc stimulation of O-glycosylation (O-glycosidic linkage between glycan and an amino acid containing a hydroxyl group [77]) when discussing the possible mechanism of diabetic complications as a consequence of increased flux through HBP [78,79]. In a recent study, we have demonstrated that serum N-glycan alterations are associated with diabetic kidney disease [40], which is further discussed below. Taken together, there is accumulating evidence for the role of HBP in both diabetes onset and diabetes complications.…”
Section: Hexosamine Biosynthesis Pathway and Its Role In Diabetes Thrmentioning
confidence: 99%
“…However, under conditions of hyperglycaemia the percentage of total glucose utilized through the HBP could be enhanced, leading to increased levels of the major product of the HBP, uridine diphosphate N ‐acetylglucosamine (UDP‐GlcNAc). This was proposed as one of the mechanisms for the observed increase in plasma levels of the highly branched N‐glycan structures in type 1 diabetes patients, type 2 diabetes patients and even healthy people at the increased risk of developing diabetes in the future .…”
Section: Hexosamine Biosynthesis Pathway and Its Role In Diabetes Thrmentioning
confidence: 99%
See 2 more Smart Citations
“…The alterations of glycosylation could affect the immune system of mammals 37 . The relationship between abnormal glycosylation and the pathogenesis of diabetes has also been reported 38 . In this dataset, decreases in the abundance of HexNAc modified peptides were detected in NO patients compared to CO subjects (p=0.048 by a two-sample, two-tailed t-test) (Figure 6b).…”
Section: Resultsmentioning
confidence: 98%